The Income Capitalization Approach for property valuation: a critical assessment of opportunities and limitations (Architecture Image Studies, 2026)
The article provides a critical analysis of income-based methods used in real estate valuation (the Income Capitalization Approach – ICA) with the aim of highlighting their theoretical foundations, operational applications, strengths, and limitations within increasingly complex real estate markets. The study adopts a comparative approach based on an examination of the theoretical assumptions and operational procedures underpinning the methodologies included in the ICA. Critical variables are evaluated, such as the definition of cash flows, the determination of capitalization and discount rates, the estimation of terminal value, and the reliability of market inputs. The investigation integrates insights from international literature and reflections derived from professional practice. The critical assessment shows that Direct Capitalization (DC) remains effective in stable and transparent markets, but proves rigid in contexts characterized by irregular income patterns, cyclicality, or limited information availability. Discounted Cash Flow (DCF) analysis emerges as a more flexible and theoretically robust methodology capable of modeling complex scenarios; however, its effectiveness is strongly dependent on the quality of the assumptions adopted and on market predictability.The article offers an interpretative framework that can guide both academic research and professional practice toward a more informed, transparent, and critical use of income-based valuation tools.